THE PROCUREMENT CONTRACT RESPONSIBILITIES IN BLANGPIDIE DISTRICT COURT: AN ANALYSIS OF BAI MUSAWWAMAH THEORY - Annisa Syahla Nazhira; Muhammad Ahsan (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
This study aims to analyze the responsibility of PT. Juang Awe Karya (PT. JAK) in the procurement contract for goods at the Blangpidie District Court, Southwest Aceh, from the perspective of Bai' Musawwamah theory. Bai' Musawwamah is a buying and selling principle that emphasizes agreement on price and product specifications through deliberation, which is relevant in public procurement practices that prioritize transparency and fairness. The method used in this study is a juridical-empirical approach with a descriptive qualitative method, collecting data through interviews and direct observation of relevant parties, such as the management of PT. JAK and the Blangpidie District Court. The results of the study show that the procurement contract has been carried out according to the principles of Bai' Musawwamah, with clear agreements on price and specifications. However, PT. JAK experienced a violation in the form of delayed delivery of goods, which resulted in sanctions as stipulated in the contract. PT. JAK’s responsibilities include the obligation to provide goods according to specifications and on time, as well as to replace or repair goods if quality issues arise. The application of the Bai' Musawwamah principle in this contract ensures transparency, fairness, and open communication between the Blangpidie District Court and PT. JAK, as well as dispute resolution through deliberation. This study is expected to contribute to the understanding of the application of Islamic principles in procurement and its impact on the relationship between suppliers and consumers of goods.